Performance Evaluation of Four Activated Partial Thromboplastin Time Reagents - Yuzaqi, Peppi Z.; Halimah, Eli; Noviani, Tatat (Universitas Padjadjaran, Indonesia, 2018)
Activated Partial Thromboplastin Time (APTT) is a hematological examination to identify hemostatic abnormalities. This study aimed to compare the performance evaluation of four APTT reagents, i.e., CK Prest, Pathromtin SL, Actin SL, and Cephascreen. The methods used were photo optical, percent detection, and viscosity-based detection system (VDS). The analysis was performed on blood specimen of 43 subjects. The results indicated that the accuracy and precision in normal plasma control using C. K. Prest reagent in Coag-A-MateÂ® MTX II were d% -0.605 and CV% 2.252%, Pathromtin SL reagent in CA 560Â® (SysmexÂ®) were d% 6.9345 and CV%1.687, Actin FSL reagent in CA 560Â® (SysmexÂ®) were d% -1.51 and CV% 1.74, and Cephascreeen reagent in STA CompactÂ® were d% 10.81 and CV% 1.60. The accuracy and precision in pathological plasma control using Pathromtin SL reagent in CA 560Â® (SysmexÂ®) were d% -1,11 and CV% 8.82, Cephascreen reagent in STA CompactÂ® were d% 4.64 and CV% 2.72. The coefficient of correlation between C. K. Prest reagent and Pathromtin SL reagent was 0.880 with the regresion equation y=2.31xâ33.70. The coefficient of correlation between C. K. Prest reagent and Actin FSL reagent was 0.986 with the regretion equation y=0.78x+2.93. The coefficient of correlation between C. K. Prest reagent and Cephascreen reagent was 0.987 with the regretion equation y=1.70xâ3.97. In conclusion, the best precision was obtained from Cephascreen reagents in STA compactÂ®devices for both normal and pathologic control plasma, with eligible accuracy.Keywords : Activated Partial Thromboplastin Time (APTT), Photo-optical, Viscosity-based Detection System (VDS)